DESULFURIZATION OF FLUE GASES OF THERMAL POWER PLANTS WITH OBTAINING POTASSIUM-MAGNESIUM FERTILIZER (KALIMAGNESIA) - Olha Khatsevych; Sofiia Fedorchenko; Sergiy Kurta; Ihor Mykytyn; Olha Derzhko (Environmental Problems)
A new method of flue gas desulfurization with the production of a valuable is proposed. The essence of the method is to pass flue gases through a scrubber (Venturi) filled with magnesium hydroxide suspension. At the same time, SO2of the flue gases will react with magnesium hydroxide according with the formation of magnesium sulfite. Crystals of magnesium sulfite are able to interact with new portions of SO2 and turn into hydrosulfite. As a result of such “washing” of flue gases, a suspension of sparingly soluble salt MgSO3·6H2O in a 12–15 % solution of MgSO4 is obtained. Magnesium hexahydrate will precipitate as large crystals and be separated in a hydrocyclone. Separated crystals of magne-sium sulfite will be oxidized under the influence of air oxygen to magnesium sulfate.